2003
DOI: 10.1111/1467-8268.00061
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Relationship between Cash Flow and Dividend Changes in Nigeria

Abstract: The purpose of this study is to re-evaluate the incremental information content of cash flows in explaining dividend changes, given earnings. I carry out an 882 firm-year study by analysing the dividend changes-cash flow relationship on a sample of 63 quoted firms in Nigeria over a wider testing period from 1984 to 1997. Despite the fact that I used a wider testing period than previous studies and more refined cash flow measures than previous studies, I also introduced dummy variables to capture economic polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 28 publications
3
54
0
4
Order By: Relevance
“…Previous studies on the dividend decision of Nigerian companies have either employed aggregated regression analysis to examine the determinants of dividend policy or were conducted more than 30 years ago (Soyode, 1975;Oyejide, 1976;Ariyo, 1983;Adelegan, 2003). The Nigerian investment environment has witnessed significant changes since the return to democratic rule in 1999.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Previous studies on the dividend decision of Nigerian companies have either employed aggregated regression analysis to examine the determinants of dividend policy or were conducted more than 30 years ago (Soyode, 1975;Oyejide, 1976;Ariyo, 1983;Adelegan, 2003). The Nigerian investment environment has witnessed significant changes since the return to democratic rule in 1999.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Yeo (2018) examined the role of free cash flow in making investment and dividend decisions in shipping industries, employing generalized least square regression, and the result revealed that free cash flow leads to an increase in investment and reduction in dividends among a sample of 137 shipping firms from 35 countries. Although there is series of studies in Nigeria that examined the relationship between dividend policy and other variables like firm performance, share price, life-cycle theory, cash flow, and agency conflict among which are, Adelegan (2003), Tijjani & Sani (2016), Eniola & Akinselure (2016), Ogundipe et al (2012), Nwidobie (2013), Bingilar & Oyadonghan (2014), Inyiama & Nwankwo (2016), Okafor et al (2011). We could not find any study in Nigeria that directly tested the validity of the free cash flow hypothesis among firms trading in the Nigerian stock exchange.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…It acts as a monitor, and maintains discipline in the firm. It is believed that the decision of the board is supreme (Fama and Jensen, ; Adelegan, ). The findings show that there is a positive and significant relationship between board size and dividend policy.…”
Section: Review Of Literaturementioning
confidence: 99%